Shape and size engineered cellulosic nanomaterials as broad spectrum anti-microbial compounds - Sharma, Priyanka R.; Kamble, Sunil; Sarkar, Dhiman; Anand, Amitesh; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2016)
Oxidized celluloses have been used for decades as antimicrobial wound gauzes and surgical cotton. We now report the successful synthesis of a next generation narrow size range (25-35 nm) spherical shaped nanoparticles of 2,3,6-tricarboxycellulose based on cellulose I structural features, for applications as new antimicrobial materials. This study adds to our previous study of 6-carboxycellulose. A wide range of bacteria such as Escherichia coli, Staphloccocus aureus, Bacillus subtilis and Mycobacterium tuberculosis (non-pathogenic as well as pathogenic strains) were affected by these polymers in in vitro studies. Activity against Mycobacteria were noted at high concentrations (MIC99 values 250-1000 mu g/ml, as compared to anti-TB drug Isoniazid 0.3 mu g/ml). However, the broad spectrum activity of oxidized celluloses and their nanoparticles against a wide range of bacteria, including Mycobacteria, show that these materials are promising new biocompatible and biodegradable drug delivery vehicles wherein they can play the dual role of being a drug encapsulant as well as a broad spectrum anti-microbial and anti-TB drug. (C) 2016 Published by Elsevier B.V.
Keywords: Anti-microbial; cellulose; Spherical nanoparticles; Tricarboxycellulose

Antimicrobial and antioxidant potential of a standardized ayurvedic formulation explains its clinical efficacy as gargles in post-radiotherapy oral cancer patients - Chavan, Sandeep; Bhuvad, Sushama; Kumbhlakar, Bhagyashri; Auti, Jyoti; Walunj, Tanhaji; Pathak, Shridevi; Tanpure, Rahul; Gujar, Shweta; Shinde, Jagdish; Kulkarni, Arvind; Gupta, Vidya; Deshmukh, Vineeta; et al. (Journal of Herbal Medicine, 2021)
Introduction: Exploring the antioxidant and antimicrobial potential of a standardized proprietary poly-herbal powder and evaluating its clinical efficacy as an Ayurvedic gargle (Gandush) for reducing oral microbial load and side effects of radiotherapy in oral cavity cancer patients was the aim of this pilot study. Methods: Formulation (Gandush Churna) comprising Terminalia chebula Retz., Terminalia bellirica (Gaertn.) Roxb., Phyllanthus emblica L. and Curcuma longa L. and its decoction (Gandush Kwath) were standardized. In-vitro antioxidant potential and antimicrobial activity against selective bacterial and fungal strains were studied. Oral cavity cancer patients who had undergone radiotherapy were enrolled. The decoction was prepared by soaking Gandush Churna in water, boiling and reducing by 50 %; and was used for gargling, twice a day, for 7 days. Total microbial count and identification of microbiota in the oral cavity as well as symptoms graded as per Common Terminology Criteria for Adverse Events, were noted before and after the treatment. Change in microbial load and shift in symptom gradations were analyzed. Results: A monograph with physicochemical, chromatography, safety and stability parameters was developed. The decoction possessed good in-vitro antioxidant and antimicrobial activities. Gargling therapy significantly reduced bacterial load while mildly controlled the fungal infection in oral cavity cancer patients. It significantly reduced the severity of symptoms viz. stomatitis and local pain, with considerably decreased xerostomia and dysphagia. Conclusions: Intervention of gargle therapy using poly-herbal formulation may serve as an effective complementary treatment to improve oral hygiene and reduce side effects of radiotherapy in oral cancer patients.
Keywords: Anti-microbial; Antioxidant; Gandush; Gargle therapy; Oral cavity cancers; Radiotherapy side effects